PEMBELAJARAN PRAKARYA SEBAGAI PROSES BUDAYA DALAM ANTROPOLOGI PENDIDIKAN SEKOLAH DASAR - Putri Zaera, Sonia; Rahmad Syah Putra; Bansu Irianto Ansari; Ummu Kholifatul Khasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Craft learning in elementary schools is not only oriented toward the development of students’ motor skills and creativity, but also functions as a medium for cultural learning from the perspective of educational anthropology. This article aims to examine craft learning as a cultural process that represents the values, symbols and social practices of local communities within the educational context.This study employs a descriptive qualitative approach through a literature review and analysis of craft learning practices in elementary schools. The findings indicate that craft learning plays a role as a medium for cultural transmission, the strengthening of local identity, and the internalization of social and cultural values among students. Based on these findings, craft learning has a strategic role in integrating education and culture, as well as supporting social transformation in elementary schools.